CURRICULUM DEVELOPMENT FOR CROSS-MADHHAB FIQH INSTRUCTION IN MODERN ISLAMIC BOARDING SCHOOLS - Ahmad Rifa’I Arif; Syafuri; Muhajir; Ahmad Fitriyadi Sari; Wasehudin; Yahdinil Firda Nadirah; Ade Fakih Kurniawan (Program Studi Manajemen Pendidikan Islam, 2026)
Islamic boarding schools (pesantren) in Indonesia, particularly in Banten, play a central role in transmitting Islamic knowledge, especially fiqh. However, the dominance of a single school of thought often results in limited exposure to diverse Islamic legal perspectives. This study aims to: (1) examine the philosophical foundation for developing cross-madhhab fiqh materials in modern pesantren based on the Kulliyatul Mu‘allimin al-Islamiyyah (KMI) system; (2) analyze the current implementation of cross-madhhab fiqh learning in Banten; and (3) formulate a systematic development model. Using a Research and Development (R&D) approach with the Dick and Carey model, the study followed ten stages from needs analysis to field testing. Data were collected through observation, interviews, documentation, and questionnaires, and analyzed qualitatively and quantitatively. The findings show that the philosophical foundation of cross-madhhab learning is rooted in religious moderation, respect for classical jurisprudence, and responsiveness to contemporary needs. However, implementation remains limited, often confined to final-grade students and dominated by the Bahtsul Masail method. The proposed model integrates fiqh muqaran (comparative), maqasid al-shari‘ah, and problem-based learning, supported by cross-madhhab references and case-based evaluation. The model effectively enhances students’ understanding, tolerance, and active participation, offering a relevant framework for inclusive fiqh education